2024
DOI: 10.1039/d4nr00606b
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of dual defect modified graphitic carbon nitride is robust to tautomerism: machine learning assisted ab initio quantum dynamics

Sraddha Agrawal,
Bipeng Wang,
Yifan Wu
et al.

Abstract: Two-dimensional graphitic carbon nitride (GCN) is a popular metal-free polymer for sustainable energy applications due to its unique structure and semiconductor properties. Dopants and defects are used to tune GCN,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…DISH takes into account the quantum decoherence of the electronic subsystem, giving rise to trajectory branching . The decoherence time scale is estimated as the pure dephasing time of the optical response theory. , Quantum transitions take place in the DISH algorithm as a result of the decoherence process and take place at decoherence effects, establishing the physical foundation for hops. ,, This methodology has been successfully applied to investigate photoexcitation dynamics in various systems, including semiconducting quantum dots, plasmonic nanoparticles, , black phosphorus, , transition metal dichalcogenides, graphitic carbon nitride, 2D layered halide perovskites, 3D organic–inorganic perovskites and their interfacial or grain boundary systems, , single-atom catalysts, ordered magnetic systems, etc.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…DISH takes into account the quantum decoherence of the electronic subsystem, giving rise to trajectory branching . The decoherence time scale is estimated as the pure dephasing time of the optical response theory. , Quantum transitions take place in the DISH algorithm as a result of the decoherence process and take place at decoherence effects, establishing the physical foundation for hops. ,, This methodology has been successfully applied to investigate photoexcitation dynamics in various systems, including semiconducting quantum dots, plasmonic nanoparticles, , black phosphorus, , transition metal dichalcogenides, graphitic carbon nitride, 2D layered halide perovskites, 3D organic–inorganic perovskites and their interfacial or grain boundary systems, , single-atom catalysts, ordered magnetic systems, etc.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The current energy demand around the globe has intensified the research for clean and renewable energy technologies that can directly abate the continuous deterioration of the environment by achieving zero CO 2 emissions. In this context, the utilization of solar energy for photocatalysis and photoelectrochemical (PEC) water splitting has attracted an extensive amount of research interest. In recent times, scientists have focused on photoactive metal oxides as emerging materials owing to their low cost, facile synthesis, and long-term stability. In the past few years, there has been an enormous amount of interest in the development of heterojunction-based composite materials, with enhanced photoactivity and redox ability. , It has been reported that the selection of materials for heterojunction formation based on their respective band edge positions is crucial to achieve favorable charge carrier dynamics. , In a typical PEC system, the hydrogen evolution reaction (HER) occurs at the photocathode [H + /H 2 at 0 V vs the reversible hydrogen electrode (RHE)], while the photoanode is responsible for the oxygen evolution reaction (OER, O 2 /H 2 O at 1.23 V vs the RHE) . Both photocatalysis and PEC water splitting involve the generation of electrons and holes under light, followed by their transport to the surface.…”
mentioning
confidence: 99%
“… 1 5 In this context, the utilization of solar energy for photocatalysis and photoelectrochemical (PEC) water splitting has attracted an extensive amount of research interest. 6 9 In recent times, scientists have focused on photoactive metal oxides as emerging materials owing to their low cost, facile synthesis, and long-term stability. 10 12 In the past few years, there has been an enormous amount of interest in the development of heterojunction-based composite materials, with enhanced photoactivity and redox ability.…”
mentioning
confidence: 99%